In vivo evidence of outer hair cell length changes and their role in high-frequency cochlear mechanics - Puria, Sunil; Cho, Nam Hyun; Guinan, John J. (Frontiers in Audiology and Otology, 2025)
IntroductionThe great sensitivity and frequency selectivity of mammalian hearing originates in cochlear mechanics. Cochlear responses to sound are thought to be amplified by outer hair cells (OHCs) cyclically expanding and contracting lengthwise in response to audio-frequency changes in their transmembrane potential. The mechanism by which OHCs amplify sound in the cochlea remains an enigma. Individual OHCs in micro-chambers have low-pass current-to-displacement characteristics with corner frequencies of a few kHz. In vivo, OHC corner frequencies were estimated to be 3 kHz. Since cochlear motion is amplified at many tens of kHz, the low OHC corner frequency appeared to be a problem for high-frequency amplification to be produced by OHC cyclic length changes.MethodsWe compared OHC motion to BM motion using high-resolution optical-coherence-tomography (OCT) in the 38–46 kHz best-frequency (BF) region of Mongolian gerbils. We measured transverse organ-of-Corti (OoC) motions at the OHC top near the reticular lamina (RL), at the OHC bottom near the OHC-Deiters-cell junction (ODJ), and at the basilar-membrane (BM). From these in-vivo measurements we determined the transverse (lengthwise) motions of individual OHCs.ResultsAt moderate tone levels and at frequencies up to 40–50 kHz, the motions at the top and bottom of the OHCs were almost exactly out of phase, consistent with motion generated by OHC motility. Furthermore, OHCs length changes were greater than BM motion at frequencies of 40–50 kHz.DiscussionThus, a low OHC current-to-displacement corner frequency should not be viewed as preventing OHCs from adding energy cycle-by-cycle to overcome cochlear damping and provide cochlear amplification. Our results are consistent with cochlear amplification being produced by OHC motility at all frequencies.